1977
DOI: 10.1079/bjn19770066
|View full text |Cite
|
Sign up to set email alerts
|

Determination of rumen microbial growth in vitro from32P-labelled phosphate incorporation

Abstract: 1. The extracellular phosphate pool in incubations of rumen fluid or washed cell suspensions of mixed rumen bacteria (WCS) was labelled with 32P. From the constant extracellular phosphate pool specific activity and the amount of radioactivity incorporated during incubation, the amount of P incorporated in the microbial fraction was calculated. From the value for nitrogen: P determined in microbial matter, the amount of N incorporated was calculated as a measure of microbial growth. 2. Incorporation of soluble … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
40
1
6

Year Published

1980
1980
2014
2014

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(52 citation statements)
references
References 53 publications
5
40
1
6
Order By: Relevance
“…Such predation is probably not accounted for by Pirt-like maintenance equations (Hobson and Wallace, 1982) as it necessitates the adaptation of mathematical models for continuous culture (Smouse, 1981). The detrimental role of protozoa in rumen microbial N yield was speculated upon in earlier work (review in Demeyer, 1981) and demonstrated by the determination of simultaneous total synthesis and degradation of microbial matter in vitro (Van Nevel and Demeyer, 1977) using faunated and defaunated mixed rumen microorganisms . The absence of protozoa lowered degradation and slightly increased total synthesis, resulting in a considerable increase of net synthesis (e.g.…”
Section: The Presence Of Protozoamentioning
confidence: 99%
See 2 more Smart Citations
“…Such predation is probably not accounted for by Pirt-like maintenance equations (Hobson and Wallace, 1982) as it necessitates the adaptation of mathematical models for continuous culture (Smouse, 1981). The detrimental role of protozoa in rumen microbial N yield was speculated upon in earlier work (review in Demeyer, 1981) and demonstrated by the determination of simultaneous total synthesis and degradation of microbial matter in vitro (Van Nevel and Demeyer, 1977) using faunated and defaunated mixed rumen microorganisms . The absence of protozoa lowered degradation and slightly increased total synthesis, resulting in a considerable increase of net synthesis (e.g.…”
Section: The Presence Of Protozoamentioning
confidence: 99%
“…Demeyer, 1977) (Cummins et al, 1983) around a mean of about 30, a figure introduced in systems for ruminant feed protein evaluation (Jarrige et al, 1978 ;Roy et al, 1977). Although experimental error is an important factor in variability (Faichney, 1975 ;Sutton, 1979 ;Ling and Buttery, 1978), recent data have permitted the conclusion that, provided rumen degradable protein is not a limiting factor of microbial growth, diets largely based on concentrates and on silage give lower E values than mixed diets (Tamminga, 1983) or forage diets Van Soest, 1982).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The best formula selected was obtained by using P-32 tracer to determine microbial protein synthesis in the rumen liquid [3,4].…”
mentioning
confidence: 99%
“…The gas production was measured every h. The pH of the medium, production of short-chain fatty acids (SCFA) and hydrogen (H 2 ) and the amount of residual substrate were estimated 2, 4, 6 h after the start of the incubation. Theoretical fermented organic matter (TFOM) was calculated from total SCFA production according to Van Nevel and Demeyer (1977).…”
mentioning
confidence: 99%